Coding Futures: Rethinking Digital Literacy Policies in Senior High Schools as Catalysts for Inclusive Economic Growth - Rini Werdiningsih; Arvy N. Osma; Eko Nursanty (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Digital literacy has become a key foundation for educational innovation and economic participation in the 21st century. As global economies transition toward digitalization, integrating digital competencies into senior high school curricula is increasingly viewed as essential for supporting Sustainable Development Goal 8 (SDG 8), which emphasizes decent work and inclusive economic growth. This study investigates the role of public policy in shaping digital literacy education in senior high schools through a comparative case study of Indonesia, the Philippines, and Canada. Employing qualitative policy analysis, the research explores how each country’s policy framework conceptualizes, implements, and evaluates digital literacy initiatives. The analysis focuses on curriculum integration, resource allocation, and stakeholder involvement, while also examining how these programs contribute to employability and economic resilience. The findings reveal notable differences in policy design and institutional commitment, with Canada demonstrating a more systematic integration of digital literacy, the Philippines emphasizing access and equity, and Indonesia facing challenges related to resource disparities and curriculum consistency. These variations illustrate how national contexts influence the inclusiveness and effectiveness of digital literacy policies. The study concludes with recommendations for policymakers to design context-sensitive, equitable, and future-oriented digital literacy strategies that align with labor market demands and promote sustainable economic growth.